Synthesis, characterization and 1, 3‐butadiene polymerization behaviors of cobalt complexes bearing 2‐pyrazolyl‐substituted 1, 10‐phenanthroline ligands. (27th March 2013) - Wang, Baolin; Gong, Dirong; Bi, Jifu; Dai, Quanquan; Zhang, Chunyu; Hu, Yanming; Zhang, Xuequan; Jiang, Liansheng
Abstract : A series of cobalt(II) complexes containing tridentate 2‐pyrazolyl‐substituted 1, 10‐phenanthroline ligands (L) with the general formula [LCoCl2 ] have been successfully synthesized and fully identified by IR spectroscopy, elemental analysis and mass spectroscopy. Cobalt complexes Co4–Co8 were further confirmed by X‐ray crystallographic analysis, and all the complexes adopted distorted trigonal pyramid geometries around the cobalt center. In combination with methylaluminoxane, the complexes exhibit high cis ‐1, 4‐selectivity for 1, 3‐butadiene polymerization. The catalytic activities of the complexes mainly depend on the nature of the substituent and its position at the pyrazolyl ring of the ligand. Complexes having a bulkier substituent on the pyrazolyl ring of the ligand show lower catalytic activity and the incorporation of electron‐withdrawing substituent enhances the activity. Polymerization behaviors were almost not affected with varying [Al]/[Co] ratio, but both activity and the cis ‐1, 4 content decrease slightly as polymerization temperature increasing. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A new family of Co(II) complexes bearing tridentate 2‐pyrazolyl substituted 1, 10‐phenanthroline ligands were prepared, characterized and investigated as catalyst precursor for butadiene polymerization. Highly cis ‐1, 4 selective butadiene polymerization was achieved.